Financial Benchmarking of Small and Medium Agro-Processing and Value Addition Agribusiness Enterprises in Kenya - Ndirangu, S. Njuguna (International Journal of Scientific Research and Management (IJSRM), 2017)
Financial benchmarking involves financial analysis of an enterprise and comparing the findings to otherenterprises in order to assess the competitiveness, productivity and efficiency of such enterprises. The goalis to establish the deviations from average norms and identify entry point for improving an enterpriseperformance. The study sought to compile some financial ratios that can be used in benchmarkingdifferent categories of small and medium agro-enterprises (SMAEs) and value addition agribusinesses inKenya. The ratios documented include; variable input, paid labour, power and machinery, rent andfinance, sundry overheads and net income Twenty enterprises from different sub-sectors were analysed.The sub-sectors analysed included dairy, fruits and vegetables, cereals, other livestock products, andedible nuts and oils. The data used was from an earlier findings of appraisal of SMAEs activities by theMinistry of Agriculture in Kenya. The study also has compiled findings on assessment of the improvementin performance of some of the thirteen enterprises that were benchmarked using some earlier given ratiosand which were capacity build based on the deviations identified during benchmarking.The study shows some variations in the ratios across the different sectors and the level of operation. It alsoindicates that financial benchmarking can provide an entry point to upscaling the performance of SMAEs.The data acquired in the study can be used to benchmark both small and medium agro-processing andvalue addition agribuiness enterprises.